Linear models for stockpiling in open-pit mine production scheduling problems - Moreno, Eduardo; Rezakhah, Mojtaba; Newman, Alexandra; Ferreira, Felipe (European journal of operational research, 2017)
•We propose new linear models for modeling stockpiles in open pit mining.•We compare how their assumptions affect solution quality and tractability.•These models include blending requirements without unrealistic assumptions.•Experiments show that our proposed models are tractable and yield good approximations. The open pit mine production scheduling (OPMPS) problem seeks to determine when, if ever, to extract each notional, three-dimensional block of ore and/or waste in a deposit and what to do with each, e.g., send it to a particular processing plant or to the waste dump. This scheduling model maximizes net present value subject to spatial precedence constraints, and resource capacities. Certain mines use stockpiles for blending different grades of extracted material, storing excess until processing capacity is available, or keeping low-grade ore for possible future processing. Common models assume that material in these stockpiles, or “buckets,” is theoretically immediately mixed and becomes homogeneous. We consider stockpiles as part of our open pit mine scheduling strategy, propose multiple models to solve the OPMPS problem, and compare the solution quality and tractability of these linear-integer and nonlinear-integer models. Numerical experiments show that our proposed models are tractable, and correspond to instances which can be solved in a few seconds up to a few minutes in contrast to previous nonlinear models that fail to solve.